Offseason Workout Recommendations for Baseball Players - Klein, Brooks (Curr Rev Musculoskelet Med, 2021)
PURPOSE OF REVIEW: Offseason training programs are crucial for the baseball athlete. Preparation for the competitive season should be carefully planned to allow long-term athletic success. The two goals of the offseason training program are to optimize performance and reduce injury risk. These goals can only be accomplished with an understanding of the unique physical demands of the sport, and how these demands relate to performance and injury. The purpose of this article is to review the unique demands of baseball training along with current strength and conditioning principles to optimize offseason training for the baseball athlete. RECENT FINDINGS: Traditional strength and conditioning programs used in other sports may not maximize the qualities necessary for optimal baseball performance. Traditional strength and conditioning exercises, such as squat and deadlift, primarily train sagittal plane movement while frontal and transverse plane movements are likely equally as important for baseball players. Biomechanical studies have shown that trunk rotation power has the largest influence on throwing velocity in pitchers. Programs should also be designed to reduce injury risk for common injuries. The most common injuries in baseball include hamstring strains, throwing arm injuries, paralumbar muscle strains, hip adductor strains, and oblique muscle strains. SUMMARY: This review describes the typical periodization phases of the offseason and provides a sample program outlining an offseason program for a professional baseball player from September through February.